WILLIAM SHAKESPEARE'S TRAGEDIES - Ibragimova Dilafruz; Toirjonova Xushnoza Niyozmamat qizi (Journal of Innovation in Education and Social Research, 2024)
This article discusses the characteristic and artistic features of the genre of tragedy on the example of Shakespeare's work and "Hamlet" tragedy. Shakespearean tragedy is the story of suffering and calamity of the tragic hero. These suffering and calamities are exceptional and so affect the whole nation. In Shakespearean tragedy chance and fate plays important role. In Shakespearean tragedy supernatural elements like ghosts and witches also play important role.